KONTROVERSI PEMBANGUNAN TEMPAT PENAMPUNGAN SEMENTARA (TPS) DI KABUPATEN TULUNGAGUNG MENURUT TINJAUAN HUKUM - Melando, Antonius Sepsia; Winardi, Brezillya Anggraini; Wicahyo, Tito Tirto; Ardiansyah, Pramana (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The problem regarding the existence of waste in the Tulungagung Regency area, until now has been classified as having no end and beginning, there are always cases of pollution every day, at every time, in every condition. This is due to inappropriate waste management by the government, and the lack of public awareness of waste management. This study uses a normative juridical research approach. Which aims to discuss how the implementation of laws and regulations regarding waste management and environmental management for the construction of Temporary Shelters in several places in Tulungagung Regency. Based on the results of this study, it can be concluded that the construction of temporary shelters in Tulungagung is still not in accordance with the laws or regulations. This can be seen from the negative impacts caused by the existence of temporary shelters